A Quick Method for Screening Platelet Dysfunctions Using the Whole Blood Lumi-Aggregometer - Ingerman-Wojenski, Carol M; Silver, Melvin J (Thrombosis and Haemostasis, 1984)
Patients who present with a clinical history suggesting a bleeding disorder are often tested initially for a clotting defect rather than for platelet dysfunction, due to the length of time necessary to complete a platelet function study in platelet-rich plasma. We have developed a sensitive method for measuring platelet aggregation and release of ATP employing the Whole Blood Lumi-Aggregometer. This method makes it possible to quickly detect patients who require further study for possible platelet function disorders such as cyclooxygenase deficiency, storage-pool defect, thrombasthenia, and von Willebrand’s disease. The results obtained with this electrical impedance instrument do not differ from those obtained with the conventional optical method. However, it is now possible to recognize a platelet function defect within 30 min of obtaining a 5 ml sample of citrated whole blood. Further, platelets of unusual size or density are not lost to testing through centrifugation.
Keywords: Platelet aggregation; Release reaction; Electrical impedance method; Platelet dysfunction